Two alternative recessive quantitative trait loci correlate with resistance to spring black stem ad leaf spot in Medicago truncatula - Kamphuis, L.; Lichtenzveig, Judith; Oliver, Richard; Ellwood, Simon (BioMed Central Ltd, 2008)
Background: Knowledge of the genetic basis of plant resistance to necrotrophic pathogens is incomplete and has been characterised in relatively few pathosystems. In this study, the cytology and genetics of resistance to spring black stem and leaf spot caused by Phoma medicaginis, an economically important necrotrophic pathogen of Medicago spp., was examined in the model legume M. truncatula.